Campanian Ignimbrite tephra reveals asynchronous vegetation responses to abrupt climate change in the eastern Mediterranean region - McGuire, Amy; Lane, Christine S.; Roucoux, Katherine H.; Lawson, Ian T.; Koutsodendris, Andreas; Pross, Jörg; Margari, Vasiliki; Tzedakis, Polychronis C. (Quaternary science reviews, 2024)
The timing and rate of ecosystem response to abrupt climate change is a product of numerous complex interactions between biotic and abiotic drivers. Palaeoecological studies from long sedimentary records, particularly those that span periods of dynamic climate such as the last glacial cycle, can help to contextualise ecosystem responses to climate variability through time. Detailed studies that compare proxy data from multiple sites, with high chronological precision, have the potential to ascribe mutual climate drivers, and, therefore, track spatiotemporal variability in ecosystem responses. Here, we interrogate the vegetation impact of past climate change in the eastern Mediterranean, using three sub-centennially resolved pollen archives from Greece. The widespread Campanian Ignimbrite (CI/Y-5; ca. 39.85 ka BP) tephra marker is used as an isochron to directly correlate pollen records from Ioannina (NW Greece), Tenaghi Philippon (NE Greece), and Megali Limni (NE Aegean). Our results reveal spatiotemporal variability in the timing of vegetation response in the Mediterranean to climate forcing across Heinrich Stadial 4 (40.2-38.3 ka BP), a period of known abrupt climatic change. We identify a decline in tree pollen in all three sites, likely related to the onset of enhanced regional aridity, with vegetation at Tenaghi Philippon responding prior to the CI/Y-5, in contrast to at Megali Limni and Ioannina, where much of the vegetation change occurs following tephra deposition.
Online verfügbar: 27. Mai 2024
Gesehen am 27.11.2024